Assessing Professional Caregivers’ Intention to Use and Relatives’ Support of Use for a Mobile Service Robot in Group Therapy for Institutionalized People with Dementia – A Standardized Assessment Using an Adapted Version of UTAUT - Wasic, Catharina; Bahrmann, Frank; Vogt, Stefan; Böhme, Hans Joachim; Grässel, Elmar (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2022)
Introduction: Care settings for people with dementia involve not only the individuals who are being cared for but also professional caregivers and relatives. Therefore, the use of a social robot also depends on professional caregivers’ and relatives’ acceptance of the robot. Methods: We surveyed 29 relatives and 18 professional caregivers of institutionalized people with dementia in a nursing home in Germany. To assess acceptance, we used an adapted version of the Unified Theory of Acceptance and Use of Technology and the Almere model. Results: Intention to use the robot by professional caregivers correlates positively with attitude, facilitating conditions and perceived usefulness as well as negatively with anxiety. Support of use by relatives correlates positively with attitude, perceived usefulness, facilitating conditions and social influence. Intention to use and support of use significantly differ between professional caregivers and relatives. Conclusion: For professional caregivers and relatives that are not the primary users of the robot and only indirectly affected by the employment of a robot, perceived usefulness and attitude have a significant influence on the acceptance. Professional caregivers are more skeptical about social robots and have lower acceptance values compared to relatives.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Acceptance; Caregivers; Dementia; Residential facilities; Robotics

Feasibility, acceptance, and impact of socially assistive robots in non-drug interventions with people with dementia: A scoping review - Wasic, Catharina; Pendergrass, Anna; Böhme, Hans Joachim; Bahrmann, Frank; Grässel, Elmar (Gerontechnology, 2020)
Background: With increasing research on robotics, socially assistive robots may broaden potential forms of non-drug interventions for the increasing numbers of people with cognitive impairments. Existing reviews have concentrated on one robot, one intervention, or one outcome only. With this paper, we attempt to gain an overarching perspective on different types of socially assistive robots in various non-drug interventions, and their feasibility, acceptance, and impact. Objective: We conducted a scoping review of research on socially assistive robots used in non-drug interventions for people with dementia (PwDs) or people with mild cognitive impairment (PwMCIs) to determine whether the use of robots is feasible, accepted, and yields a positive impact on the attendees. Methods: We used the online databases PubMed, CINAHL, and IEEE Xplore to identify relevant studies published up to the end of 2018. To be included, studies had to involve PwDs/PwMCIs and deploy a robot in a non-drug intervention. Ambient Assisted Living (AAL) structures were excluded. Results: This review included a total of 70 records with 21 different robots (12 animaloids, 4 humanoids, 5 mechanoids). The findings indicated that feasibility is a necessity for acceptance, which in turn is a necessity to generate an impact. Robots are feasible as long as they function and as long as non-cognitive symptoms (e.g. agitation) do not get in the way of conducting the intervention. Results for acceptance were mixed, but generally, PwDs and PwMCIs were interested in interacting with the robots. No coherent positive impacts other than increased communication, engagement, and pleasure were found. Neither cognitive nor other non-cognitive symptoms of PwD/PwMCI were significantly positively influenced by controlled studies. Conclusions: Firstly, more research should focus on feasibility and acceptance. Secondly, studies examining possible impacts need to be better structured and comparable.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Cognitive Dysfunction [MeSH]; Dementia [MeSH]; Non-drug Intervention; Review [MeSH]; Robotics [MeSH]

Predictors of intensity of use of adult day care centers in people with cognitive impairment - Wasic, Catharina; Grässel, Elmar; Luttenberger, Katharina; Donath, Carolin (Zeitschrift für Gerontologie und Geriatrie, 2021)
Background Adult day care is an established concept in Germany for people with cognitive impairment; however, only a small fraction of people in need for care actually use adult day care. Studies so far highlighted some predictors for the use of adult day care; however, it remains unclear which factors are associated with the intensity of use. Objective To identify relevant predictors for the intensity of use of adult day care using the Andersen healthcare utilization model. Material and methods Data used were obtained within the project dementia in day care with psychosocial MAKS interventions (DeTaMAKS), which studied adult day care users with cognitive impairments and their family caregivers. A logistic regression was performed to predict frequent or low use of adult day care. Results The following factors were significantly associated with higher intensity of use: civil status of adult care user being widowed or single, higher educational level of caregiver, higher care level, longer duration of adult day care use and more mental and behavioral symptoms of the adult day care user. The sensitivity analysis for cohabiting dyads additionally showed a higher intensity of use with a lower age of the caregiver and shorter distance between place of residence and adult day care but not with respect to educational level of the caregiver and mental and behavioral symptoms of the user. Conclusion The results show a need for adult day care, which increases with caregivers being employed and users living outside of permanent relationships. A short distance to the adult care center as well as flexible care options may increase the frequency of use.
CRIS-Team WoS Importer:2021-10-08

Psychosocial Multi-component Intervention for People with Dementia: Comparison with and without Robotic Assistance - Dirks, Kaja; Wasic, Catharina; Grassel, E. (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2022)
CRIS-Team WoS Importer:2022-09-16

What helps, what hinders?—Focus group findings on barriers and facilitators for mobile service robot use in a psychosocial group therapy for people with dementia - Wasic, Catharina; Erzgräber, Robert; Unger-Büttner, Manja; Donath, Carolin; Böhme, Hans Joachim; Grässel, Elmar (Frontiers in Robotics and AI, 2024)
Introduction: Many countries are facing a shortage of healthcare workers. Furthermore, healthcare workers are experiencing many stressors, resulting in psychological issues, impaired health, and increased intentions to leave the workplace. In recent years, different technologies have been implemented to lighten workload on healthcare workers, such as electronic patient files. Robotic solutions are still rather uncommon. To help with acceptance and actual use of robots their functionalities should correspond to the users’ needs. Method: In the pilot study Care4All–Initial, we developed and field-tested applications for a mobile service robot in a psychosocial, multimodal group therapy for people with dementia. To guide the process and assess possible facilitators and barriers, we conducted a reoccurring focus group including people with dementia, therapists, professional caregivers as well as researchers from different disciplines with a user-centered design approach. The focus group suggested and reviewed applications and discussed ethical implications. We recorded the focus group discussions in writing and used content analysis. Results: The focus group discussed 15 different topics regarding ethical concerns that we used as a framework for the research project: Ethical facilitators were respect for the autonomy of the people with dementia and their proxies regarding participating and data sharing. Furthermore, the robot had to be useful for the therapists and attendees. Ethical barriers were the deception and possible harm of the people with dementia or therapists. The focus group suggested 32 different applications. We implemented 13 applications that centered on the robot interacting with the people with dementia and lightening the workload off the therapists. The implemented applications were facilitated through utilizing existing hard- and software and building on applications. Barriers to implementation were due to hardware, software, or applications not fitting the scope of the project. Discussion: To prevent barriers of robot employment in a group therapy for people with dementia, the robot’s applications have to be developed sufficiently for a flawless and safe use, the use of the robot should not cause irritation or agitation, but rather be meaningful and useful to its users. To facilitate the development sufficient time, money, expertise and planning is essential.
CRIS-Team Scopus Importer:2024-07-12
Keywords: dementia; focus group; institutional care; robot-assisted therapy; user-centered design

Wunsch und Wirklichkeit: Diskrepanz zwischen tatsächlicher und beabsichtigter Nutzung von ambulanten Entlastungsangeboten - Scheerbaum, Petra; Grässel, Elmar; Wasic, Catharina; Pendergrass, Anna (Gesundheitswesen, Supplement, 2024)
Aim In Germany, people in need of care are mainly cared for by their relatives who make use of various outpatient relief and support services. The aim of this study was to determine the frequency of actual use as well as the desired use of outpatient relief and support services. Dementia and non-dementia as causes behind need for care are distinguished. Methods A representative sample of informal caregivers of statutorily insured care recipients assessed by the MD Bayern during application for a care level classification (n = 958) was analyzed. The use of the following outpatient relief and support services was investigated: outpatient care service; domestic help; day care centre; meals on wheels; driving service; care service; 24-hour care; and care group. Characteristics of the care receiver, the informal caregiver and the care situation were recorded. Difference analyses were carried out using Chi2 tests and t-tests. Results The use of outpatient support services was low despite the high care burden on informal caregivers ranging from 1,7 % for the care group to 38,4 % for the outpatient care service. More than 40 % of respondents did not use any of the eight services. However, from this non-user group, 72 % had a desire to use at least one of the eight services in the future. Domestic help and outpatient care services were the most frequently requested services by non-users. Actual and desired use was more common for dementia than for other causes of need for care, especially for day care, care group and care service. Conclusion The desire for utilization is significantly higher than the reality of utilization. In general, the use of outpatient relief and support services is low. The causes of this discrepancy need to be explored. Therefore, effective strategies need to be developed to advise informal caregivers which ensure suitable respite services will be used to strengthen the home care situation.
CRIS-Team Scopus Importer:2024-03-08
Keywords: care receivers; informal caregivers; long term care; outpatient geriatric care; outpatient support services